Relationship of prop (6-n-propylthiouracil) taster status of Filipino women with their preference and sensory responses to umami, salty and umami-salty foods and food model systems - Tria, Ma. Celina D.; Villarino, Blanca J. (c2011.)
ABSTRACT This study mainly aimed to determine the PROP taster status of randomly selected Filipino women and to evaluate the influence of PROP taster status on their preference and sensory responses to umami, salty and umami-salty foods and food model systems. The randomly selected respondents (n=50) accomplished a food preference checklist and rated the intensities of PROP and NaCl solutions using a labeled magnitude scale (LMS) for PROP taster classification. Likewise, the recruited panelists evaluated the intensities and acceptance of five solutions representing the umami, salty and umami-salty food model systems using the LMS and nine-point hedonic scale, respectively. The subjects were found to be 8% non-tasters, 30% medium tasters and 62% supertasters. No significant (p>0.05) correlation exists between PROP sensitivity and food preferences for umami, salty and umami-salty foods and food model systems. Likewise, PROP sensitivity had no association (p>0.05) with the intensity and hedonic responses for the three food model systems except for the negative correlation (p<0.05) with the overall acceptance of 55:45(%w/v) solution of the umami-salty food model systems. Intensity ratings were found to be significantly (p<0.05) correlated with acceptability ratings for most samples in all the three food model systems. Based from the findings on the relationship between intensity ratings and acceptability scores grouped by PROP taster status, supertasters could be at risk for obesity, while non-tasters are highly susceptible to hypertension.
Thesis(BSFT)--University of the Philippines Diliman
Keywords: Senses and sensation -- Testing; Umami (Taste)